An updated checklist of the amphibian diversity of Maliau Basin Conservation Area, Sabah, Malaysia - Alexander Haas; Kueh, Boon Hee; Alvinus Joseph; Masliadi Asri; Indraneil Das; Reto Hagmann; Loraine Schwander; Stefan T. Hertwig (2018)
The current account presents the results of a 14-day amphibian survey at Maliau Basin Conservation Area (MBCA). With a total of approximately 170 man-hrs, 44 species were detected at four study sites during the field period; four more species were later discovered outside the two-week campaign. The results are compared to the results of previous surveys. Apart from adults, we present the first photographic documentation of the larval stages of Chiromantis inexpectatus and Bornean Phrynoidis juxtaspera, along with a brief tadpole description; the better-known tadpoles of four more species were recorded. The results of our expedition suggest that nine more species are present at MBCA than reported by previous studies. We present an updated list of known species in the MBCA, comprising 61 species. The species accumulation curve over the 14 days period of the core survey did not show signs of asymptotic saturation. We conclude that the definitive species number for MBCA amphibians has the potential to increase with more thorough surveys in the future.